Effects of abrupt changes between mash and pellet diets on growth performance in finishing pigs - C B Paulk; J C Ebert; J J Ohlde; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 2011)
A total of 200 finishing pigs (average initial BW of 132.3 lb) were used in a 58-d growth assay to determine the effects of an abrupt change from mash to pellets and pellets to mash on growth performance and carcass measurements. The experiment was designed as a randomized complete block with 5 pigs per pen and 10 pens per treatment. There were 4 treatments with 2 phases of diets utilized. Treatments were mash to mash, mash to pellets, pellets to mash, and pellets to pellets for Phases 1 and 2 of the experiment. For Phase 1 (d 0 to 36), pigs fed the pelleted diet had 4% greater (P<0.06) ADG and F/G was improved (P<0.03) by 8% compared to pigs fed mash. For Phase 2 (d 36 to 58) and overall (d 0 to 58), pigs fed the mash diet had poorer (P<0.01) F/G than pigs fed the pelleted treatments. Indeed, pigs fed pellets the entire experiment had ADG and F/G 5 and 8% better (P<0.01), respectively, than pigs fed mash the entire experiment. Pigs fed mash during Phase 1 then pellets during Phase 2 had improved (P<0.01) ADG and F/G for Phase 2 compared with pigs fed pellets then mash. Overall pigs fed pellets for either Phase 1 or 2, but not both, tended to have poorer (P<0.10) ADG and F/G compared with pigs fed pellets for the entire experiment. With HCW used as a covariate, no differences (P>0.15) were observed in dressing percentage, fat thickness, loin depth, or percentage fat-free lean index (FFLI). Pigs fed pellets tended to have the greatest growth performance, pigs fed mash the worst, with pigs fed pellets for only part of the grow-finish phase rating intermediate.; Swine Day, Manhattan, KS, November 17, 2011
Keywords: Swine Day; 2011; Kansas Agricultural Experiment Station contribution; no. 12-064-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1056; Swine; Meal; Pelleting; Finishing pig